2012
DOI: 10.1063/1.4753898
|View full text |Cite
|
Sign up to set email alerts
|

Power rating of CPV systems based on spectrally corrected DNI

Abstract: Power rating based on two different spectroheliometers with lattice-matched (LM) and upright metamorphic (UMM) component solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…4 and similar to the work by Germany and Spain [3,4]) can achieve an outdoor power rating with approximately ±2.5% variation. These results are based on SMR filtering of ±5% and at least 10 "acceptable days" of data.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…4 and similar to the work by Germany and Spain [3,4]) can achieve an outdoor power rating with approximately ±2.5% variation. These results are based on SMR filtering of ±5% and at least 10 "acceptable days" of data.…”
Section: Resultsmentioning
confidence: 70%
“…Specifically, it has been indicated that the spectral matching ratio, SMR (the ratio of the current generated in the top reference cell to the current in the middle reference cell under the G173 reference spectrum), will be used to determine if a data point is acceptable for use in the power rating procedure. Groups from Germany and Spain have indicated that this method has promise for minimizing the impact of spectral variation [3,4], but a clear procedure for using SMR in achieving a low uncertainty power rating has yet to be written and tested.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of this approach is that the spectral effects of an HCPV device are quantified by adjusting only the incident DNI [58].…”
Section: Application Of Anns To Estimate the Electrical Characteristimentioning
confidence: 99%
“…A different approach for electrical modelling of these devices is based on the premise that the electrical parameters of an HCPV module can be estimated by applying models and equations used for conventional PV technology from the DNI, corrected spectrally, and the T c [58,59]. According to this approach, two ANNs for estimating these parameters have been proposed in [41,60].…”
Section: Application Of Anns To Estimate the Electrical Characteristimentioning
confidence: 99%
“…From the photocurrents of a set of component cells we can define the so called Equivalent Irradiance for each subcell [4], as the normalized current to the reference spectrum and irradiance:…”
Section: Spectral Matching Ratio (Smr)mentioning
confidence: 99%